Acute toxicity of Trigonella foenum-graecum (Fenugreek) seeds aqueous extracton liver in male mice, histopathological study - Hamad Alfarisi, Hamad Abdulsalam; Allow, Ahmed Kaid Naji; Hamdan, Asmah Hanim; Hamad Mohamed, Zenab (Moksha Publishing House, 2017)
Acute toxic effect of fenugreek on liver histology has not been fully explored. Hence the objective of this study is to investigate the acute toxicity of fenugreek seeds aqueous extract (FSA) on liver histology. Twelve male Swiss albino mice, were randomly divided into control (C), and three treatment (T1, T2, and T3) groups (n = 3 each). T1, T2, and T3 were given 3g, 6g, and 9g/kg body weight FSA respectively. Intragastric divided doses of FSA were given as per OECD guidelines 425. Continuous observation of signs of acute toxicity and survival set up. The mice were euthanized on day 14 and the liver was dissected and processed for histopathological examination. 3, 6, and 9g/kg body weight FSA doses failed to induce any of signs of acute toxicity. Histopathological examination revealed that, all FSA administered doses showed mild portal inflammation, mild mononuclear cell infiltration in hepatic parenchyma, in addition to mild bile stasis induced only in mice received 9g/kg of FSA. Administered doses of FSA showed mild liver histopathological inflammatory changes.